Association between serum albumin and cognitive dysfunction in hepatic encephalopathy: An exploratory data analysis. Issue 2 (7th December 2020) - Kaji, Kosuke; Okita, Kiwamu; Suzuki, Kazuyuki; Sato, Ikuya; Fujisawa, Masaki; Yoshiji, Hitoshi
Abstract: Background and Aim: Because covert hepatic encephalopathy (CHE) has been shown to affect the prognosis of cirrhotic patients, early diagnosis of hepatic encephalopathy (HE) is a prerequisite for the preservation of patients' quality of life and for prophylaxis of overt HE. The aim of this study was to identify a clinical parameter to predict impairment of cognitive function in cirrhotic patients with early‐stage HE. Methods: We investigated the data from 172 patients with cirrhotic or idiopathic portosystemic shunt (PSS) in phase II/III trials of rifaximin in Japan. Classification and regression trees (CARTs) were constructed to identify clinical profiles related to cognitive dysfunction as indicated by the prolongation of time required for the Number Connection Test (NCT‐B). Results: CART analysis detected age 65 years as the variable for the initial split, and serum albumin level was selected as the variable for the second split among patients aged ≤65 years. In 27 cirrhotic patients aged ≤65 years without PSS, receiver operating characteristic curve analysis revealed that the optimal albumin level cutoff point was 3.05 g/dL, and the area under the curve was 0.80 for the prolongation of NCT‐B time, which was higher than that of the branched‐chain amino acids‐to‐tyrosine ratio (0.46), the prothrombin time–international normalized ratio (PT‐INR) (0.68), serum ammonia (0.61), and total bilirubin (0.69). Conclusions: Lower serum albumin level as a clinical biomarker associated with impaired cognitive function may be available as a screening examination for early‐stage HE in cirrhotic patients aged ≤65 years without PSS before undergoing neuropsychological tests. Abstract : The aim of this study was to identify a clinical parameter to predict the prolongation of time required for the Number Connection Test (NCT‐B), a measure of cognitive function, in patients with early‐stage HE. A lower level of serum albumin was the major clinical parameter related to liver cirrhosis that was associated with prolongation of the time required for the NCT‐B in cirrhotic patients aged 65 years.